The Lattice Mismatch-Driven Photochemical Self-Assembly of Supported Heterostructures for Stable and Enhanced Electrocatalytic Carbon Dioxide Reduction Reaction - Yidan Liu; Xu Ren; Yali Ji; Ting Li; Rongrong Jia; Liyi Shi; Wenlong Zhou; Xiran Qiao; Lei Huang (Molecules)
Metallic heterostructural nanocrystals (HNCs) hold immense potential in electrocatalytic carbon dioxide reduction reaction (CO2RR) owing to their abundant active sites and high intrinsic activity. However, a significant challenge still remains in achieving controlled nucleation and growth sites for HNCs on supports and comprehending the influence of the structure–activity relationship on electrocatalytic CO2RR performance. This work presents a photochemical self-assembly technique without the necessity for reducing agents or facet-specific capping agents. By controlling lattice mismatch and manipulating transfer paths of photo-generated carriers, we can precisely direct the growth sites and nucleation of nanocrystals, enabling the self-assembly of supported core–shell and Janus nanostructures. Compared to Pd(T)@Au core–shell HNCs with the same loading, Pd cube–Au Janus HNCs exhibit significantly enhanced selectivity and stability toward carbon monoxide (CO) production in CO2RR at less negative potentials. The Pd cube–Au Janus HNC electrocatalyst achieved a Faradaic efficiency (FE) of 92.6 ± 3.5% for CO electroreduction, accompanied by a current density of 72.3 mA·cm−2 at −0.58 V. This work provides an effective strategy for designing advanced supported tandem electrocatalysts to boost the selectivity and durability test of CO2RR.